Changes in pulmonary exercise haemodynamics in scleroderma: a 4-year prospective study. Issue 1 (13th July 2017) - Kovacs, Gabor; Avian, Alexander; Wutte, Nora; Hafner, Franz; Moazedi-Fürst, Florentine; Kielhauser, Sonja; Aberer, Elisabeth; Brodmann, Marianne; Graninger, Winfried; Foris, Vasile; Olschewski, Andrea; Olschewski, Horst
Pulmonary arterial hypertension (PAH) is a feared complication of systemic sclerosis. In this prospective cohort study, we monitored the changes in resting and exercise pulmonary haemodynamics of scleroderma patients without initial PAH over a mean follow-up period of ∼4 years. All patients underwent exercise echocardiography and cardiopulmonary exercise testing at baseline and follow-up. A subgroup underwent exercise right heart catheter (RHC) investigations. The primary end-point was the echocardiographic systolic pulmonary arterial pressure at 50 W exercise (sPAP50 ). We included 99 patients, of whom 58 had a complete dataset. Three out of 99 patients developed RHC-confirmed PAH (0.75 cases per 100 patient-years). sPAP50 increased (p<0.001) and peak oxygen uptake (secondary end-point) decreased significantly (p=0.001) during follow-up, but there was no significant change in resting sPAP (p=0.38). In the RHC subgroup (n=28), mean (m)PAP and pulmonary vascular resistance at 50 W increased significantly (p=0.02 and p=0.002, respectively), but resting mPAP was unchanged. Scleroderma patients without PAH develop a mild but significant deterioration of pulmonary exercise haemodynamics and exercise capacity over a 4-year follow-up period, indicating a progression of pulmonary vascular disease. The manifestation rate of RHC-confirmed PAH was 0.75 cases per 100 patient-years. Scleroderma patients without pulmonary hypertension develop mild deterioration in pulmonary exercise haemodynamics http://ow.ly/hva930aEW4E